GENETIC OPTIMIZATION ANALYSIS OF WIND TOWER VIBRATIONS CONTROLLED BY A PENDULUM TMD - Colherinhas, Gino Bertollucci; Morais, Marcus Vinicius Girão; Shzu, Maura Angélica Milfont; Ávila, Suzana Moreira (Revista Interdisciplinar de Pesquisa em Engenharia, 2017)
The wind turbine is supported by towers, which are slender and flexible due to their geometry and great height. As a consequence, they may experience excessive vibration levels caused by both the operation of the turbine and the wind loads. One common passive control device to solve this problem is the Tuned Mass Damper (TMD). Briefly, it is a pendulum-damper which transfers the energy of the vibration from the main structure to itself, working as a passive device. These passive devices need to be finely tuned to work as dampers, otherwise, they could amplify structural vibrations levels. The objective of this paper was create a project methodology to optimize a pendulum + mass-spring (2-DoF) structural model. The mass, length, stiffness, and damping coefficient of the pendulum were the parameters surveyed for this optimization. We carry out a map of high vibration amplitudes describing the dynamic behavior of the 2-DoF structural model. This map was used to validate 2-DoF’s GA optimization results. Then we compared the finite element models (BEAM and SHELL) obtained integrating the commercial platform ANSYS with the MATLAB toolbox. A project methodology was reached to define optimum absorber configurations.